(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Total 60 patients were selected as per described criteria from the department of Otolaryngology and head neck surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2005 to October 2006. In this study of 60 patients of differentiated thyroid carcinoma (DTC), majority of the patients are within 31-50 yrs age group with female predominance. Papillary carcinoma was more common in 31-40 yrs age group and follicular carcinoma was more common in 41-50 years. Thyroid swelling was the most common presenting symptom of DTC (91.66%), followed by cervical lymphadenopathy (33.33%). Among the 60 DTC patients, papillary carcinoma was commoner (73.33%) than follicular carcinoma (26.67%). Overall female-male ratio for these 60 patients of DTC was 1.72: 1, but in papillary type the ratio was 1.44:1. and for follicular carcinoma was 3:1. Out of 44 papillary carcinoma patients 18 patients had cervical lymph node metastasis (40.90%), and out of 16 follicular carcinoma patients 2 had cervical lymph node metastasis (12.50%); P < 0.05. Among the 44 papillary carcinoma patients only 1 had distant metastasis (2.27%), and among the 16 follicular carcinoma patients 4 had distant metastasis (25%); P <0.05. 85% of the patients were presented with unilateral and 15% were presented with bilateral lymph node metastasis. In this series, distant metastasis was found in bone and lung, Maximum lymph node metastasis was found in level II (42.10%), level III (57.89%) and level IV (42.10%). Finally the Chi-square (x2) significance test was performed according to above described findings and it was found that there is significant difference in the pattern of lymph node metastasis and of distant metastasis between papillary and follicular type of DTC (P<0.05). Key words: Thyroid carcinoma; Metastasis. DOI: 10.3329/bjo.v15i2.5059 Bangladesh J Otorhinolaryngol 2009; 15(2): 60-68